O discurso do bem-estar na revista Vida Simples : simplicidade ou sofisticação? - Perfeito, Denise Gasparini (Universidade Federal de São Carlos, 2016)
This paper aims to investigate the way Vida Simples magazine talks about what we call welfare discourse from an interdiscoursive approach as proposed by Dominique Maingueneau registered under French Discourse Analysis. The analysed material consists of thirteen editions of this magazine: issues published between June and April 2014 and the first issue published in August 2002. Data revealed that with lightness and relaxation, this magazine orients to a life based on /simplicity/, presenting itself in a clean and sophisticated graphic pattern, very different from other magazines with the same profile. Thus, we can observe there is a tension between /simplicity/ and /sophistication/ established in Vida Simples pages. This tension is conditioned by the global semantic that governs the materialized discourse in it as a whole, which gives meaning to what seem unacceptable: welfare is in simplicity and /simplicity/ is a sophisticated acquisition of specific goods that produce an image, a face, an identity. Although this magazine takes an affectionate and amused discursive ethos to refer to a better and not complicated life (since there are pre-built ideas pointing to Contemporaneity as difficult and highly complicated life), we can say this guidance discourse, stimulated by the environment of malaise of Contemporaneity, paradoxically (and constitutively) includes incentives to maintenance of sales market, a cultural characteristic of consumer society.
Keywords: Discurso do bem-estar; Ethos discursivo; Semântica global; Sociedade de consumo; Welfare discourse; Discursive ethos; Global semantic; Consumer society; CIENCIAS HUMANAS::EDUCACAO